Design of feasibility study for the establishment of production of zirconium-89 radioisotope and implementation of of 89 Zr-radiopharmaceuticals in clinical practice in the Republic of North Macedonia - Katerina Kolevska; Marija Atanasova-Lazareva; Maja Chochevska; Maja Velichkovska; Filip Jolevski; Tripunoski, Toni; Memeti, Shaban; Ugrinska, Ana; Bistra Angelovska (My University, 2023)
In the last decade, the application of radiopharmaceuticals based on zirconium-89 (89Zr) radiometal has increased in both preclinical and clinical studies. The most frequently used 89Zr-radiopharmaceutical is 89Zr-trastuzumab used in the management of patients with breast cancer. Breast cancer is the most common cancer among women in North Macedonia and the most common cause of death from malignant neoplasms in this population; therefore, the introduction of new nuclear medicine procedures in these patients might improve the management of this disease. However, the introduction of radioisotope and radiopharmaceutical production requires significant investments, both manpower and financial. The purpose of this work is to present the design conceptualization of a feasibility study for the establishment of production of zirconium-89 radioisotope and implementation of 89Zr-radiopharmaceuticals in clinical practice in the Republic of North Macedonia and to present the initial results from the first phases of the study. This feasibility study is designed to include preliminary analysis, market research, technical feasibility analysis, economic analysis, review and analysis of all data and feasibility conclusion. The evaluation of the data from the analyses conducted in all study phases is needed to identify the favourable and unfavourable factors and circumstances in order to make a final assessment of the feasibility of establishing the zirconium-89 radioisotope and 89Zr-radiopharmaceuticals production and implementation of 89Zr-trastuzumab use in nuclear medicine practice.
Keywords: feasibility study; zirconium- radioisotope; Zr-radiopharmaceuticals; Zr-trastuzumab